Role of Rare-Earth Cerium in Martensitic Transformation and Magnetic Properties of Cu-Al-Mn Alloys - Ozkul, Iskender; Kalay, Ece; Karaduman, Oktay; Kizilgun, Yasin; Guler, Omr; Canbay, Canan Aksu (Springer, 2025)
This study investigates the effects of different cerium additions on the properties of Cu-Al-Mn high-temperature shape memory alloy (HTSMA), such as the characteristic martensitic transformation temperatures, transformational kinetic parameters, and martensitic microstructures which are related to its shape memory mechanism and also to its magnetic behavior. Polycrystalline alloys with a base composition of Cu77.32Al21.02Mn1.67 (at.%) were synthesized, and varying concentrations of cerium (Ce-1 to Ce-4) were added for comparison. Differential scanning calorimetry tests revealed notable increments in transformation temperatures with cerium additions. Specifically, the austenite start temperature of the reference alloy increased from 143.75 degrees C to 194.88 degrees C by 0.05 at.% of Ce addition (Ce-3 alloy), corresponding to the formation of CeCu5 and Mn1.15Cu3.85Ce phases. However, excessive Ce addition in Ce-4 led to the over-stabilization of secondary phases, reducing the transformation temperatures. Microstructural analysis indicated that Ce addition of refined grains changed the crystallite size of the martensite structure and reduced lattice strain (from 0.72% to 0.34%). Magnetic characterization demonstrated that Ce addition shifted the alloy towards paramagnetic behavior, with M-H curves showing no significant coercive field or remanent magnetization across the studied alloy samples. These findings suggest that cerium can enhance the high-temperature performance of Cu-Al-Mn HTSMAs, with potential applications in environments requiring both shape memory and magnetic properties.
Keywords: Shape-Memory Alloys; Mechanical-Properties; Ce Addition; Grain-Size; Microstructure; Temperature; Texture